In the eye of the storm: exploring the introduction of environmental issues in the production function in Brazilian companies - Chiappetta Jabbour, Charbel Jose [UNESP] (Taylor & Francis Ltd, 2010)
This article aims to analyse the introduction of environmental issues in the context of the production function, which has been referred to as the organisational area to lead corporate environmental management. With that purpose, the theoretical references for corporate environmental management and the necessary alterations in production function have been organised to include environmental aspects, especially in terms of product and process development, quality management, and logistics. Considering that this research field still lacks empirical evidence for Brazilian companies, four case studies were conducted using companies located in the country. The environmental management maturity level of those companies tends to follow the rate with which the environmental issue is introduced in production sub-areas, especially in the product development process. However, in most cases we found that the companies had difficulties in structuring the insertion of the environmental dimension in logistics. The final notes point out the distance observed between what is recommended by international literature and the reality of Brazilian companies in the challenge of making the production function environmentally friendly.
Keywords: environmental management; production function; product development; sustainability; Brazilian companies